Evaluation of Indonesian Government Policies in Addressing Climate Change and Natural Disasters - Sarjito, Aris (Jurnal Ilmu Sosial dan Humaniora, 2023)
Climate change and natural disasters pose significant challenges to countries around the world. The Indonesian government has implemented various policies to address climate change issues and mitigate the impact of natural disasters. However, the effectiveness and impact of these policies remain unclear. This research aims to evaluate the current policies implemented by the Indonesian government in addressing climate change issues and mitigating the impact of natural disasters. It also aims to identify the key challenges faced by the Indonesian government in policy implementation and assess the effectiveness of these policies in reducing climate change risks and mitigating the impact of natural disasters in Indonesia. Additionally, potential areas for strengthening and improving government policies will be explored. A qualitative research method will be adopted, utilizing secondary data sources such as reports, academic journals, and government publications. These sources will be analyzed to gain insights into the current policies and their effectiveness. The research finds that the Indonesian government has implemented several policies to tackle climate change issues and natural disaster mitigation. Key challenges faced include limited resources, a complex bureaucratic structure, and difficulties in enforcement. While the current policies have had some impact in reducing climate change risks and mitigating the impact of natural disasters, their effectiveness is hindered by these challenges. The evaluation suggests the need for strengthening and improving Indonesian government policies on climate change and natural disaster mitigation. This includes enhancing resource allocation, streamlining bureaucratic processes, and improving enforcement mechanisms.